2022
DOI: 10.3389/ftox.2022.933186
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic organisms modulate the bioreactivity of engineered nanoparticles: focus on biomolecular corona

Abstract: The increased use of nanoparticle (NP)-enabled materials in everyday-life products have raised concerns about their environmental implications and safety. This motivated the extensive research in nanoecotoxicology showing the possibility that NPs could cause harm to the aquatic organisms if present at high concentrations. By contrast, studies dealing with influence that organisms could exert on the fate and thus effects of NPs are still very rare. Drawing on the existing up-to-date knowledge we critically disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 123 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…Given the existing knowledge about the role of freshwater EPS in the fate and transformations of metal-containing nanoparticles [123], it is anticipated that they could significantly affect the bioreactivity of NPLs. Indeed, the need to incorporate the concept of the biomolecular corona into a broader framework that considers interactions and feedback between phyto-and zooplankton in response to nanoparticles exposure has been highlighted [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the existing knowledge about the role of freshwater EPS in the fate and transformations of metal-containing nanoparticles [123], it is anticipated that they could significantly affect the bioreactivity of NPLs. Indeed, the need to incorporate the concept of the biomolecular corona into a broader framework that considers interactions and feedback between phyto-and zooplankton in response to nanoparticles exposure has been highlighted [69].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have highlighted how phytoplankton influence the bioavailability of NPLs through the excretion of various EPS, forming the eco-corona [68,69]. EPS, ubiquitous in the environment [70], can account for up to 25% of natural organic matter in freshwater ecosystems, particularly during algal blooms [71].…”
Section: The Phytoplankton Feedback On Npls Bioavailability and Toxicitymentioning
confidence: 99%
“…In order to prevent denaturation and loss of function due to protein/enzyme binding of NPs, enzyme molecules are combined and cross-linked together to form NPs in a prearranged manner. This method has succeeded in unlocking the manufacturing potential of biosensors with increased analytical performance (Riley & Narayan, 2021;Liu et al, 2022;Thapa et al, 2022). In addition, recent research indicates that enzyme NPs exhibit high catalytic efficiency and thermal stability, which enhances both the temperature resistance and cellulose degradation capacity of these NPs (Khizar et al, 2021;Gu et al, 2022;Liu et al, 2022).…”
Section: Advantages Of Nano-sized Feed Additivesmentioning
confidence: 99%
“…Recent in vitro and animal studies have shown that excessive accumulation of NPs can damage cellular organs such as the liver, spleen, kidneys, and respiratory tract and cause toxic effects (Surendhiran et al, 2020). Further research is needed to assess the potential risks to human and animal health and the environment from exposure to NPs (Liu et al, 2022).…”
Section: Potential Risks In Animal Nutritionmentioning
confidence: 99%
“…Engineered nanoparticles (ENPs) have dimensions ranging from 1 to 100 nm (Vert et al, 2012), and possess unique properties which make them highly valuable for various applications in technology, medicine, environment and consumer products (Zhang et al, 2016;Mitchell et al, 2021;Keller et al, 2023). When released into freshwater environment, ENPs can undergo a variety of physical and chemical transformations (Levard et al, 2012;Batley et al, 2013;Yu et al, 2018;Wheeler et al, 2021;Liu et al, 2022;Rex M et al, 2023). The interconnected transformation processes determine collectively the environmental behavior and effects of ENPs on aquatic biota (French et al, 2009;Fernando and Zhou, 2019;Khort et al, 2022).…”
Section: Introductionmentioning
confidence: 99%